Usefulness of Simple-Designed Bilobed Flap for Reconstruction of Ischial Decubitus Ulcer - Iida, Naoshige (Plast Reconstr Surg Glob Open, 2015)
The pressure ulcer of the ischial region is often accompanied by complete paraplegia in patients with spinal cord injury and is attributable to the compression and breakdown of tissue arising from constant sitting. Characteristically, a pressure ulcer of this region is circular and deep. We recently reconstructed ischial decubitus ulcer of 8 patients using simple-designed bilobed flap. In all cases, the flap survived completely without any complication. Moreover, none of the patients in this group experienced any pressure ulcer relapse during the postoperative follow-up from 1 year 1 month to 9 years. In the vicinity of the ischial region, the buttock contains the most abundant amount of fatty tissue. Therefore, for our technique, we create the first flap in the buttock neighboring the defect and the second flap on the posterior thigh. Using this approach, it is possible to cover the skin or soft tissue defect of the ischial region with the flap from the buttock having a thickness large enough to bear the patient’s weight during sitting. The first flap is arranged parallel to the gluteal sulcus, and the second flap from the thigh is moved to the first-flap donation site. This technique allows closure of the wound without producing tension along the suture line. The bilobed flap, which does not require the artery to be included in the flap, is applicable for patients with relapsing pressure ulcer having a history of surgery. Our flap operative procedure is particularly useful in the reconstruction of ischial decubitus ulcer.